“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Le Pont Victoria, un lien vital / Victoria Bridge, the vital link - Triggs, Stanley (Musée McCord d'histoire canadienne, 1992)
Keywords: Ponts; Victoria (pont)

Le Pont / The Bridge - Triggs, Stanley G. (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

Le Cadre / The Setting - Young, Brian (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

L'inauguration / The Celebration - Graham, Conrad (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

L'impact / The Impact - Lauzon, Gilles (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

Le Pont Victoria. Le lien vital - Kennell, Elizabeth H. (Montréal, une histoire à suivre, 1992)
Translators: _:n34924
Keywords: Ponts; Victoria (pont)

Victoria Bridge. The Vital Link - Kennell, Elizabeth H. (Montreal, a History to Treasure, 1992)
Translators: _:n34943
Keywords: Ponts; Victoria (pont)

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Le pont tubulaire et ferroviaire Victoria - Pratt, Michel (Histoire Québec, 2010)
Number: 1
Keywords: Chemins de fer; Ponts; Victoria (pont)

Hunter's Hand-Book of the Victoria Bridge... A Brief History of that Wonderful Work - Boxer, F. N. (Hunter, 1860)
Keywords: Chemins de fer; Grand Tronc; Ponts; Victoria (pont)

Le chemin de fer sur la glace - Lefort, Pierre (Histoire Québec, 2000)
Number: 1
Keywords: Canadien Pacifique; Chemins de fer; Longueuil; Ponts; Victoria (pont)